The Classifications and Syntactic Structures of English sentences in K-pop song lyrics - , RAHAJENG HANDARU SUMMA; , Dr. F.X. Nadar, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims at ascertaining the dominant types of sentence and the sentence structure which are made by Korean, as non-native speakers of English, by analyzing the English lines in K-pop song lyrics which are in the form of sentences. The objectives of the research are to classify the English sentences based on the classification of sentences by Marcella Frank and to represent the syntactic structure of the sentences which are classified in the dominant sentence types. The data source for this research are fifty two K-Pop songs which rank first on Gaon Monthly Singles Chart from January 2009 until May 2013. The methods employed to represent the syntactic structures of the English sentences are tree diagram system and phrase structure rules (PS rules) proposed by Herman Wekker and Liliane Haegeman. The results of the sentence classifications show that declarative sentences dominate the English sentence classification by types with 59% and simple sentences dominate the English sentence classification by the number of formal predications with 81%. Based on the result of representing the syntactic structures of the dominant sentence type, there are three patterns of PS rules found from the total 79 simple declarative English sentences as follows: SâNP-VP, SâNP-NP-VP and SâNP-VP-NP.